2009
DOI: 10.1002/qsar.200860163
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pirinixic Acids as PPARα Preferential Dual PPARα/γ Agonists

Abstract: Pirinixic acid is a moderate agonist of both the alpha and the gamma subtype of the peroxisome proliferator activated receptor (PPAR). Previously, we have shown that a-alkyl substitution leads to balanced low micromolar-active dual agonists of PPARa and PPARg. Taking a-hexyl pirinixic acid as a new scaffold, we further optimized PPAR activity by enlargement of the lipophilic backbone by substituting the 2,3-dimethylphenyl with biphenylic moieties. Such a substitution pattern had only minor impact on PPARg acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…One of those byproducts was formed in high amounts in step (iii a). It was not described in former publications concerning that type of reaction [ 6 , 8 , 10 , 11 , 12 , 13 , 14 ], also with different aromatic amines as nucleophiles, and this forced us to modify the reaction procedure as well as the way of purification. In step (iii a) the chlorinated pyrimidine derivative 5 should be monoaminated to 6 by a nucleophilic aromatic substitution with 2,3-dimethylaniline.…”
Section: Resultsmentioning
confidence: 99%
“…One of those byproducts was formed in high amounts in step (iii a). It was not described in former publications concerning that type of reaction [ 6 , 8 , 10 , 11 , 12 , 13 , 14 ], also with different aromatic amines as nucleophiles, and this forced us to modify the reaction procedure as well as the way of purification. In step (iii a) the chlorinated pyrimidine derivative 5 should be monoaminated to 6 by a nucleophilic aromatic substitution with 2,3-dimethylaniline.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, PPAR activation was merely affected. A very potent PPAR agonist with excellent selectivity over PPAR (107) was obtained by replacing the central pyrimidine ring of 105 by benzene and the amine linker by a larger propane-1,3-diol moiety [124][125][126].…”
Section: -Substituted Aryloxyacetic Acid Derivatives (Fibrates)mentioning
confidence: 99%
“…Notably, the substitution pattern of the biphenyl moiety had only minor impact on the PPAR activation and the dual mPGES‐1/5‐LO inhibition. PA derivative 1 is a PPARα/γ dual agonist with an EC 50 value of 0.19 µM for PPARα and 1.5 µM for PPARγ 1. Furthermore, this compound also shows high inhibitory activities for 5‐LO (IC 50 = 0.41 µM) and mPGES‐1 (IC 50 = 1.7 µM).…”
Section: Introductionmentioning
confidence: 98%
“…1) display an interesting pharmacophore with multiple biological activities. Previously, we have shown that pirinixic acid derivatives act as activators of a subclass of nuclear receptors i.e ., peroxisome proliferator‐activated receptors (PPARs) α and γ 1–3, and as inhibitors of distinct enzymes of the arachidonic acid cascade i.e ., microsomal prostaglandin E 2 ‐synthase‐1 (mPGES‐1) and 5‐lipoxygenase (5‐LO) 4, 5. PPAR agonists are widely used drugs in the treatment of the metabolic diseases dyslipidemia (PPARα agonists like fenofibrate) and type‐2 diabetes mellitus (PPARγ agonists like pioglitazone).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation